Assessment of antimicrobial efficacy of bioceramic sealer, epiphany self-etch sealer, and AH-plus sealer against Staphylococcus aureus and Candida albicans: An In vitro study - Ruchita Kishor Rathod; Pradeep Dilip Taide; Rohan Dattatraya Dudhale (Nigerian Journal of Surgery, 2020)
Aim: The aim and objective of this in vitro study was to evaluate the antimicrobial efficacy of root canal sealers (bioceramic [BC] sealer, Epiphany self-etch sealer, and AH-Plus sealer) on Staphylococcus aureus and Candida albicans. Materials and Methods: An agar well diffusion assay method was used to determine the efficacy of the root canal sealer against S. aureus (ATCC 6538) and C. albicans (ATCC 10231). Root canal sealers were divided into three groups: BC sealer, Epiphany self-etch sealer, and AH-Plus sealer, and the standard antibiotic disc of amoxiclav and fluconazole was kept as a control against S. aureus and C. albicans. The diameters of the growth inhibition zones against S. aureus and C. albicans for each group were recorded and compared at 24 h. The differences between groups were analyzed by one-way ANOVA and Tukey's post hoc tests for intergroup analysis. Results: AH-Plus sealer exhibited a larger zone of inhibition than the other two sealers against S. aureus and C. albicans at 24 h. The standard antibiotic disc of fluconazole, which was used as a control against C. albicans, exhibited a higher antimicrobial activity than the AH-Plus sealer at 24 h, whereas Epiphany self-etch sealer showed the least antimicrobial activity against S. aureus and C. albicans. Conclusion: The AH-plus root canal sealer exhibits a better antibacterial action against S. aureus and C. albican s at 24 h.